The Neuroscience of Nonpharmacological Traditional Chinese Therapy (NTCT) for Major Depressive Disorder: A Systematic Review and Meta-Analysis - Ye, Jiajia (Evid Based Complement Alternat Med, 2019)
BACKGROUND: Depression is a common disease affecting a large number of people across the world. Many researchers have focused on treatment for depression based on Western scientific approaches, but research based on traditional Chinese medicine (TCM) interventions, studying its clinical effectiveness and the underlying mechanisms involved, has been limited. The aim of this review is to conduct a pioneering systematic review with meta-analysis of existing studies that investigate the neuroscience basis of nonpharmacological traditional Chinese therapy (NTCT). METHODS: Both English (Pubmed, Embase, Scopus, SPORTDiscus, PsycINFO) and Chinese (China National Knowledge Infrastructure (CNKI)) databases were searched from inception to October 2018. The effects of NTCT on major depressive disorder, brain activity, and neurophysiological biomarker related outcomes were extracted. Study quality was assessed using the Physiotherapy Evidence Database (PEDro) scale. The effect size of each study was reported by the mean difference of change scores. RESULTS: Six of twelve eligible studies showed that there was a significant improvement in favor of acupuncture in depressive symptoms (SMD -0.69, 95% CI -1.09 to -0.28, p=0.002, I(2) = 73%, p< 0.0008). Based on the available evidence, NTCT including acupuncture, Qigong, and Tai Chi was found to possibly improve brain metabolites, brain activity, and immune and endocrine systems in patients with major depressive disorder. CONCLUSIONS: Acupuncture could effectively relieve depressive syndromes. The clinical effects of acupuncture might be attributable to their influence on three proposed pathways, namely, the hypothalamic–pituitary–adrenal (HPA) axis, the locus coeruleus (LC)-immunity pathway, and the negative feedback loop of the hippocampus. Nevertheless, conclusions are limited due to the small number of studies included and the low-quality of the study designs. In the future, a cross-sectional study is needed to test the proposed plausible pathways. PROSPERO registration number is CRD42017080937.